CENNET MEYVELERi ÖRNEGiNDE AHiRET HAYATINA KELAMT BiR BAKlŞ - Bebek, Adil (Fırat University, 2005)
The nature of human life in the next world (akhira) has always been an important issue in the history of the islami c thought. In this artele we dealt with the life in the next world by analyzing the ftuits of paradise mentioned in Quranic versus and Prophetic traditions (hadith). First of all we explained the nations of the next world (akhira) and fiuits, then we reviewed the opinions of early islamic scholars, theologians, philosophers and modern islamic intellectuals ab out the fruits of paradi se. They interprted these fiuits differently (same literally, and some symbolicaly). At the end we saw that this disagreement comes from their understanding of religion and should not be usedas a tool for the accusation ofheresy as it was done in the past.
Keywords: Religious Studies; Din Araştırmaları